Africa's Pulse, October 2014 - Punam, Chuhan-Pole (World Bank Group, Washington, DC, 2014)
Africa’s Pulse is a biannual publication containing an analysis of the near-term macro-economic outlook for the region. It also includes a section focusing on a topic that represents a particular development challenges for the continent. It is produced by the Office of the Chief Economist for the Africa Region.This issue is an analysis of issues shaping Africa's economic future. Growth remains stable in Sub-Saharan Africa. Some countries are seeing a slowdown, but the region's economic prospects remain broadly favorable. External risks of higher global financial market volatility and lower growth in emerging market economies weigh on the downside. In several Sub-Saharan African countries, large budgetary imbalances are a source of vulnerability to exogenous shocks and underscore the need for rebuilding fiscal buffers in these countries. The Ebola outbreak is exacting a heavy human and economic toll on affected countries and, if not rapidly contained, the risk of wider contagion grows. Without a scale-up of effective interventions, growth would slow markedly not only in the core countries (Guinea, Liberia, and Sierra Leone), but also in the sub region as transportation, cross-border trade, and supply chains are severely disrupted. In Sub-Saharan Africa, growth in agriculture and services is more effective at reducing poverty than growth in industry. Structural transformation has a role to play in accelerating poverty reduction in Sub-Saharan Africa. Increasing agricultural productivity will be critical to fostering structural transformation. Boosting rural income diversification can facilitate this transformation, as well. Investments in rural public goods and services (for example, education, health, rural roads, electricity and ICT), including in small towns, will be conducive to lifting productivity in the rural economy. Although Sub-Saharan Africa's pattern of growth has largely bypassed manufacturing, growing the region's manufacturing base, especially by improving its fundamentals, lower transport cost, cheaper and more reliable power, and a more educated labor force, will benefit all sectors.